Inhibition of bone formation in rats by aluminum exposure via Wnt/β-catenin pathway. (June 2017) - Sun, Xudong; Wang, Haoran; Huang, Wanyue; Yu, Hongyan; Shen, Tongtong; Song, Miao; Han, Yanfei; Li, Yanfei; Zhu, Yanzhu
Abstract: The previous research found that aluminum trichloride (AlCl3 ) inhibited rat osteoblastic differentiation through inactivation of Wnt/β-catenin signaling pathway in vitro. On that basis, the experiment in vivo was conducted in this study. Rats were orally exposed to 0 (control group) and 0.4 g/L AlCl3 (AlCl3 -treated group) for 30, 60, 90 or 120 days, respectively. We found that mRNA expressions of type I collagen and insulin-like growth factor-1, mRNA and protein expressions of Runx2 and survivin, ratio of p-GSK3β/GSK3β and protein expression of β-catenin were all decreased, whereas the mRNA and protein expressions Dkk1 and sFRP1 and the mRNA expressions and activity of Caspase-3 were increased in the AlCl3 -treated group compared with the control group with time prolonged. These results suggest that AlCl3 inhibits bone formation and induces bone impairment by inhibiting the Wnt/β-catenin signaling pathway in young growing rats. Highlights: Dynamic analysis of exposure to AlCl3 on rats bone formation. AlCl3 inactivated the Wnt/β-catenin signaling pathway in vivo . AlCl3 inhibited rats bone formation via inactivating Wnt/β-catenin signaling pathway.